2011
DOI: 10.1073/pnas.1108431108
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic regulation of the Wingless morphogen controls sex-specific segment number in Drosophila

Abstract: Sexual dimorphism is widespread throughout the metazoa and plays important roles in mate recognition and preference, sexbased niche partitioning, and sex-specific coadaptation. One notable example of sex-specific differences in insect body morphology is presented by the higher diptera, such as Drosophila, in which males develop fewer abdominal segments than females. Because diversity in segment number is a distinguishing feature of major arthropod clades, it is of fundamental interest to understand how differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 43 publications
7
73
0
Order By: Relevance
“…In Abd-B mutants there is ectopic wg in the male A7 [15], and this is important for the formation of the segment since the Abd-B mutant phenotype is partially rescued by diminishing wg activity (Figure S4B, compare with Figure 1H). To see if emc works in the A7 by regulating wg we looked to wg expression when Emc function is compromised.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In Abd-B mutants there is ectopic wg in the male A7 [15], and this is important for the formation of the segment since the Abd-B mutant phenotype is partially rescued by diminishing wg activity (Figure S4B, compare with Figure 1H). To see if emc works in the A7 by regulating wg we looked to wg expression when Emc function is compromised.…”
Section: Resultsmentioning
confidence: 98%
“…If we elevate this activity in the male A7 we observe an increase the number of histoblasts, that many of these cells remain at the surface at the time of extrusion and that a small A7 forms in the adult. It was also previously reported that a small A7 is observed in the male adult when expressing vein , an EGFR ligand [15]. It is possible that the high number of histoblasts obtained when over-expressing elements of the EGFR pathway makes many of them unable to be extruded by a “titration” effect, that is, there may be “too many” histoblasts for the invagination mechanism to extrude them at the correct time.…”
Section: Discussionmentioning
confidence: 94%
“…These cell types derive from all primary germ layers and have diverse roles in metabolism, gametogenesis, morphology, and behavior. While the transcriptional inputs to dsx expression are not fully understood, Drosophila HOX and other patterning genes regulate dsx in at least some tissues (Foronda et al, 2012; Tanaka et al, 2011; Wang et al, 2011; Wang and Yoder, 2012; Yoder, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…These protein isoforms share a common Doublesex-Mab3 domain but contain different dimerization domains [Erdman and Burtis, 1993;Erdman et al, 1996]. As a result, female-and male-specific DSX proteins regulate a number of cytodifferentiation genes in an antagonistic manner [Burtis et al, 1991;Coschigano and Wensink, 1993;Shirangi et al, 2009;Chatterjee et al, 2011;Wang et al, 2011].…”
Section: Dsx Homologs In Lepidopteransmentioning
confidence: 99%